(untitled) (Scientific journal of the Fergana State University, 2026)
Buckwheat (Fagopyrum esculentum) is rich in biologically active substances and has a positive effect on the intestinal microflora and digestive processes. In this study, the effect of buckwheat components, in particular flavonoids (rutin and quercetin), on small intestinal enzymes was evaluated using molecular docking in the CB-Dock program. The docking results showed that rutin and quercetin form stable bonds with intestinal proteases, which can change their enzymatic activity. The pkCSM ADME/Tox platform was used to evaluate the pharmacokinetic and toxicological properties. According to the results, these flavonoids are relatively well absorbed from the intestine, do not have toxic effects, and are safely metabolized in the body. The results of the study indicate the need for further study of the beneficial properties of buckwheat for the digestive system.